967 USING CLINICAL INFORMATICS TO IMPROVE OUTCOMES AND PATIENT EXPERIENCE FOR ADMISSIONS TO WWL WITH PD AND RELATED CONDITIONS. (14th June 2022) - Alicehajic-Becic, D
Abstract: Introduction: Patients with PD depend on timely administration of their regular medication regimen to optimise their motor function. Using Clinical Informatics Database to allow analysis of medication doses, a service evaluation of PD and related conditions was undertaken using QI methodology with a particular focus on omitted and delayed doses. Alongside this, prospective qualitative data capture took place on patients' experience during hospital stay. The impact of specialist team was also analysed. Method: Using electronic prescribing records, a database of all doses for co-beneldopa was used as a starting point of identifying gaps and areas for improvement. Various interventions were implemented to address these using QI methodology. Ongoing mechanism for data capture was developed to analyse the results. Patient experience via data capture questionnaire was sought on how the changes affected their experience of hospital stay. Specialist team input was anlaysed using report on 'PD Team' notes. Results: The percentage of omissions had a mean of 10.8% from the 19, 462 doses of co-beneldopa analysed while the delays in administration improved from initial figure of 40% in 2019 to 34.7% although the trend in 8 months of 2021 increased back up to 39% (17, 313 doses of co-beneldopa). The overall total percentage of co-beneldopa doses administered had also increased (88%, 90% and 90.4% for 2019, 2020 and 2021 (Jan-Aug)). Patients reported different views on medicines management during hospital stay. PD team input more than tripled between 2019 and 2020 (192 vs 611notes) with 421 placed in 2021 up to Aug. Conclusion: Clinical Informatics data can be used to improve patient pathways and improve outcomes. Further work on patient experience will be completed to ensure their feedback is incorporated into future pathway design. Specialist input is essential in safe care of PD patients.